Legal and Administrative Sanctions for Civil Servants Engaging in Polygamy - Erwan, Erwan; Ramadhona, Suci; Yusrial, Yusrial; Sumanto, Dedi (Jurnal Elsyakhshi, 2024)
Polygamy (addud al-zaujat) has been a significant issue in husband-wife relationships throughout the history of Islamic civilization. One contributing factor to the practice of polygamy is the lack of understanding regarding its underlying reasons or motives. This study aims to analyze the sanctions imposed on Civil Servants engaging in polygamy based on the Quranic perspective in Surah An-Nisa Verse 3 and according to Indonesian Law No. 1 of 1974. The research employs a library research methodology, utilizing primary sources such as the Al-Misbah commentary and secondary sources including the Quran, Hadith, Law No. 1 of 1974, and the Compilation of Islamic Law. The findings reveal two key points. First, for civil servants practicing polygamy, the condition of fairness is emphasized. Material fairness includes equal treatment in terms of rotation, living expenses, food, clothing, and housing. However, emotional fairness, involving love and feelings of the heart, is not mandated. Second, civil servants engaging in polygamy without proper authorization face four possible sanctions: i) demotion, ii) removal from office, iii) honorable dismissal without personal request, and iv) dishonorable dismissal. Female civil servants who become a second, third, or fourth wife are subject to dishonorable dismissal from their civil service roles.